Studies on small ruminants and camels - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The International Livestock Centre for Africa (ILCA) has set up a network which groups together all the specialist researchers in the field of small ruminants and the Camelidae family. Its objectives are: to promote research for improving...